The impact of plant density on the seed yield and the spring field pea’s yield component - Krizmanić, Goran; Tucak, Marijana; Brkić, Andrija; Marković, Monika; Jovanović, Snežana V.; Čupić, Tihomir (2020)
The spring field pea is one of the most important coarse legumes. This study was carried out to investigate the response of a spring field pea variety to three plant densities (50, 100, and 150 plant m-2) during the 2017 and 2019 growing seasons in eastern Croatia. The field study was set up as a Randomized Complete Block Design (RCBD) in four replications. The results have demonstrated a significant effect of the plant densities and the growing seasons on the seed yield and on the following yield components: plant height and the number of pods/plant. The effect of plant densities on the number of seeds/pod and the thousand-seed weight was not significant. As for a growing season, the highest seed yield, plant height, the number of pods/plant were obtained in the second growing season. Furthermore, a maximum seed yield was recorded at the 150-plant m-2 plant density. This study has demonstrated that planting the spring field pea at different plant densities significantly modifies the spring field pea yield, plant height and number of pods/plant.
Jari stočni grašak jedna je od najznačajnijih krupnozrnih mahunarki. Ovo je istraživanje provedeno kako bismo vidjeli reakciju utjecaja različitih gustoća sjetve na jari stočni grašak tijekom dvaju vegetacijskih ciklusa 2017. i 2019. godine u istočnome dijelu Republike Hrvatske. Pokus je postavljen po RCBD sustavu u četiri ponavljanja. Rezultati pokazuju značajan utjecaj gustoće sjetve i godina istraživanja na prinos zrna i većinu komponenata prinosa: visinu biljke i broja mahuna po biljci, osim broja zrna po mahuni i mase tisuću zrna, gdje gustoća sjetve nije statistički značajno utjecala na razlike u vrijednostima istraživanih svojstava. Najveće vrijednosti prinosa zrna, visine biljke i broja mahuna po biljci ostvarene su u drugoj godini istraživanja. Najveći prinos zrna zabilježen je pri gustoći sjetve od 150 biljaka/m2. Istraživanje pokazuje da različite gustoće sjetve značajno modificiraju/utječu na visinu prinosa zrna i komponente prinosa jaroga stočnog graška.
Bibliografija: 25 jed.
Summary ; Sažetak.
Keywords: Jari stočni grašak -- Prinos zrna -- Gustoća sjetve